1, 3β-Glucan anchored, paclitaxel loaded chitosan nanocarrier endows enhanced hemocompatibility with efficient anti-glioblastoma stem cells therapy. (15th January 2018) - Singh, Pankaj K.; Srivastava, Anup K.; Dev, Atul; Kaundal, Babita; Choudhury, Subhasree Roy; Karmakar, Surajit
Abstract: Recurrence of glioblastoma is one of the major concerns due to its heterogeneous nature and association of Glioma Initiating stem-like Cells (GICs). Nanoparticles mediated delivery of chemotherapeutic agent targeting both cancer and glioma stem cells could provide a solution to recurrent malignancies of the glioblastoma tumor. The approach described here provides enhanced chemotherapeutic potency utilizing 1, 3 β -Glucan as an outer shell to the chitosan nanoparticles (Cs-NPs) loaded with paclitaxel to prevent hemolysis with, the core-shell nano-structure (Cs-PTX-NP) enabling effective chemotherapy against malignant glioblastoma. The prepared nanoparticles (1, 3 β -Cs-PTX-NPs) with sustained release of the paclitaxel provide a targeted therapeutic approach that overcome systemic toxicities with the 1, 3 β- Glucan shell and improve drug bioavailability. Hemolysis investigation indicated that 1, 3 β -Cs-PTX-NP was significantly less hemolytic than paclitaxel enabling intravenous delivery. Also, 1, 3 β -Cs-PTX-NPs were considerably more cytotoxic (IC50) against glioma cancer LN18 cells and C6 stem-like cells compared with the PTX. In conclusion, this study found that 1, 3 β -Cs-PTX-NP addressed serious limitation with systemic delivery of paclitaxel by preventing hemolysis and providing chemotherapeutic delivery with significant anti-cancer efficacy against recurrent glioblastoma.